THE RELATIONSHIP BETWEEN KNOWLEDGE AND MOTIVATION IN HYPERTENSION SELF-MANAGEMENT WITH BLOOD PRESSURE IN HYPERTENSIVE PATIENTS - Candra Panji Asmoro; Sriyono Sriyono; Clarita Maharani (Nurse and Holistic Care)
Introduction: The trend of increasing hypertension tends to increase and shift to a younger age. Self-management of hypertension is a strategy to help individuals with hypertension change their negative behaviour. The application of hypertension self-management is influenced by predisposing factors such as the level of knowledge and motivation.